(untitled) (Global Journal of Management and Business Research, 2019)
In this research paper the researcher focused on a different dimensions of E-commerce and its significant impact on Micro-economy. The researcher emphasized that Micro-economy is a branch of economics that studies the behavior of individuals and firms in making decisions regarding the allocation of scarce resources and the interactions among these individuals and firms. The current scenario the role of E-commerce covers the all possible dimensions of microeconomy including demand and supply, theory of production, perception of perfect and imperfect competition, defining the market structure, and game theory. The main objective of this research article is to identify the factors of E-commerce which are significantly predicted to the all possible dimensions of Micro-economy.